"Behold a Pale Horse" Blessed Mother Teresa of Calcutta and the "Experience of Nothingness". - UPSHER SMITH JR., RICHARD (Logos: A Journal of Catholic Thought & Culture)
The article focuses on the experience of nothingness by Blessed Mother Theresa of Calcutta. It says that Mother Theresa suffered the dark night of the soul after her consolations by which the Lord drew her into the ministry of the poorest of the poor. Father Brian Kolodiejchuk believes that the darkness suffered by Mother Theresa was a reparatory darkness, which helped complete Jesus Christ's sufferings on the cross for the sinners and for the poor.